2022
DOI: 10.3390/ani12172277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Cryopreservation in Farm Animals Using Nanotechnology

Abstract: Sperm cryopreservation is one of the sublime biotechnologies for assisted reproduction. In recent decades, there has been an increasing trend in the use of preserved semen. Post-thaw semen quality and values vary among animals of the same species. Similarly, there are species-specific variations in sperm morphology, i.e., sperm head, kinetic properties, plasma membrane integrity, and freezability. Similarly, the viability of sperm varies in the female reproductive tract, i.e., from a few hours (in cattle) to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 132 publications
(138 reference statements)
1
4
0
Order By: Relevance
“…However, a noticeable trend towards increased membrane integrity was noted especially at 1-2% lycopene concentrations. This observation aligns with the findings of Akhtar et al (2010Akhtar et al ( , 2022, who reported that the membrane integrity of stallion and buffalo sperm showed no significant difference following cryopreservation…”
Section: Advances In Animal Andsupporting
confidence: 92%
“…However, a noticeable trend towards increased membrane integrity was noted especially at 1-2% lycopene concentrations. This observation aligns with the findings of Akhtar et al (2010Akhtar et al ( , 2022, who reported that the membrane integrity of stallion and buffalo sperm showed no significant difference following cryopreservation…”
Section: Advances In Animal Andsupporting
confidence: 92%
“…In this work, double IP, cytoplasmatic droplets and head detachment were considered as SPZ IPD. Several studies have confirmed that sometimes it is difficult to identify which factors mainly affects frozen semen quality [43,44]. In fact, there are several factors inherent to the animal and many environmental factors as well, such as temperature, management or different SPZ cryopreservation protocols [27,29,33].…”
Section: Discussionmentioning
confidence: 99%
“…When the amount of ROS in the body goes up, it damages the DNA of sperm and makes it harder for them to fertilize eggs. During cryopreservation, ROS are made, which changes the sperm's mitochondrial membrane potential (6). Cryopreservation changes how sperm membrane lipids are made, how long they live, and how they move.…”
Section: Discussionmentioning
confidence: 99%